Application of Box-Behnken Design in Optimization of Glucose Production from Oil Palm Empty Fruit Bunch Cellulose. (3rd December 2013) - Pasma, Satriani Aga; Daik, Rusli; Maskat, Mohamad Yusof; Hassan, Osman
Abstract : Oil palm empty fruit bunch fiber (OPEFB) is a lignocellulosic waste from palm oil mills. It contains mainly cellulose from which glucose can be derived to serve as raw materials for valuable chemicals such as succinic acid. A three-level Box-Behnken design combined with the canonical and ridge analysis was employed to optimize the process parameters for glucose production from OPEFB cellulose using enzymatic hydrolysis. Organosolv pretreatment was used to extract cellulose from OPEFB using ethanol and water as the solvents. The extracted cellulose was characterized by thermogravimetric analysis, FTIR spectroscopy, and field emission scanning electron microscopy. Hydrolysis parameters including amount of enzyme, amount of cellulose, and reaction time were investigated. The experimental results were fitted with a second-order polynomial equation by a multiple regression analysis and found that more than 97% of the variations could be predicted by the models. Using the ridge analysis, the optimal conditions reaction time found for the production of glucose was 76 hours and 30 min, whereas the optimum amount of enzyme and cellulose was 0.5 mL and 0.9 g, respectively. Under these optimal conditions, the corresponding response value predicted for glucose concentration was 169.34 g/L, which was confirmed by validation experiments.